NEW DATA ON PYROCHLORE- AND PEROVSKITE-GROUP MINERALS FROM THE LOVOZERO ALKALINE COMPLEX, RUSSIA - Chakhmouradian A.R.; Mitchell R.H. (My University, 2002)
Pyrochlore- and perovskite-group minerals are relatively common accessory constituents of agpaitic murmanite lujavrites at the Lovozero alkaline complex (Russia). These rocks contain euhedral crystals of niobian calcian loparite-(Ce) and, more commonly, ceroan lueshite that occurs as discrete oikocrysts and rims on the lopat-ite-(Ce). The overall compositional range exhibited by these phases is (Na0.44-0.79 REE0.14-0.37 Cao(0.02-0.12) Sr0.04-0.09 Th0-0.01) (Nb0.12-0.66 Ti0.33-0.85 Fe0-0.01 Ta0-0.01) O-3; it agrees well with the evolutionary trend established previously for perovskite-group minerals from Lovozero. The murmanite lujavrites also contain early-crystallizing uranoan pyrochlore that subsequently underwent alteration to uranpyrochlore (5.0-26.4 wt.% UO2 for both) through interaction with a deuteric fluid. The alteration pattern involves a decrease in Na, Ca and Sr contents from the core outward, increasing ionic deficiency in the A and Y sites, and progressive hydration. The proportion of relatively higher-charged cations does not change or slightly decreases toward the rim. The occurrence of lueshite and U-bearing pyrochlore in the murmanite lujavrites indicates that these rocks crystallized from the most evolved portion of a parental phonolitic magma. Pyrochlore-group minerals also occur in albite-rich, magnesio-arfvedsonite- and aegirine-bearing metasomatic rocks. These parageneses typically contain "silicified" varieties of pyrochlore exhibiting an oscillatory zoning pattern and, in some cases, superimposed secondary zoning. The metasomatic pyrochlore ranges from nearly stoichiometric Na-Ca-rich compositions to cation-deficient strontiopyrochlore (up to 10.3 wt.% SrO) and plumbopyrochlore (up to 37.9 wt.% PbO). The oscillatory zoning involves variations in cation occupancy of the A site (primarily Na, Ca and Sr), and Si content. Elevated levels of Si (up to 16.8 wt.% SiO2) are invariably associated with the zones having the highest cation deficiency and H2O contents. A negative correlation observed between the Si and (Nb+Ti) contents is interpreted to result from changes in pH, a(SiO2) a(Na1+), a(Ca2+), and activities of minor components during the crystal growth. Primary pyrochlore-group minerals from both lujavrites and albitites are characteristically poor in Ta (< 2.6 wt.% Ta2O5), and enriched in Sr and light rare-earth elements. Comparative data on pyrochlore-group minerals from other alkaline-rock occurrences are presented.
Keywords: pyrochlore; lueshite; nepheline syenite; albitite; agpaitic rocks; Lovozero complex; Kola Peninsula; Russia